Measuring bone metabolic activity in dialysis patients with renal osteodystrophy using [18F]-Sodium Fluoride positron emission tomography- comparison between static and dynamic measurements - Aaltonen, Louise; Koivuviita, Niina; Seppänen, Marko; Oikonen, Vesa; Kirjavainen, Anna K.; Kröger, Heikki; Löyttyniemi, Eliisa; Metsärinne, Kaj (Springer Science and Business Media LLC, 2025)
Background: Dynamic [18F]NaF PET has shown promising results in the measurement of bone metabolism in patients with renal osteodystrophy. Dynamic PET scans are challenging in clinical practice, and the objective of this study was to evaluate whether standardized uptake values measured by [18F]NaF PET could be a feasible method.
Methods: Twenty-eight patients on maintenance dialysis with confirmed renal osteodystrophy underwent a dynamic [18F]NaF PET scan. As a reference for bone metabolism, a bone biopsy was obtained from the anterior iliac crest (AIC). Tracer activity in bone was measured using Patlak analysis and standardized uptake values (SUV). SUV was also adjusted to tracer activity measured from the aorta 48-60 min after injection (SUVR).
Results: SUV measured in the lumbar spine (L1-L4) and at the AIC did not correlate with histomorphometric parameters obtained by bone biopsy. There was no statistically significant difference between SUV in different turnover groups. When adjusting the mean bone uptake of fluoride in the lumbar spine, there was a strong correlation with the blood clearance of tracer to bone (Ki). SUVR also correlated significantly with histomorphometric markers obtained by bone biopsy.
Conclusions: These results suggest that measurements of tracer activity in the blood 48-60 min after tracer injection could be used to correct SUVs from static [18F]NaF PET scans. However, further research and validation of the method is needed.